Place, Capitalism, and Democratic Efficacy - Kogl, Alexandra (Conference Papers -- American Political Science Association, 2002)
Keywords: DELEUZE, Gilles; capitalism; democracy; democratic; economy; efficacy; empire; place; political; theory

The Great Transformation at Sea: Fictitious Commodities and the Crisis of Marine Fisheries - Ziegelmayer, Eric (Conference Papers -- American Political Science Association, 2002)
Challenging contemporary debates concerning the regulation of ocean fisheries, this paper deploys theoretical insights developed by Karl Polanyi. In The Great Transformation, Polanyi documented the consequences of the establishment of market economy upon European society, and thereby upon the entire planet. The concept of the self-regulating market, according to Polanyi was based on three "commodity fictions" of land, labor and money; the extension of this concept to all of the economic institutions of society he called "market utopianism." This paper extends Polanyi’s fictitious commodity thesis to the living resources of the ocean and argues that the roots of the contemporary problems of the world’s fisheries originate in the exposure of nature to a market economy. Concerned with the future governance of ocean resources and democracy in fishery regulation, the paper examines the globalization of the fishing industry in comparative and historical perspective to illuminate the validity of Polanyi’s theory. While there can be no final agreement as to the constitution of "good society", a useful starting point for debate is provided by the work of Karl Polanyi. A good society, he claims, is a society capable of producing goods, and a necessary condition of life in such a society is that human beings and nature are not treated as commodities
Keywords: capitalism; democracy; economy; fictitious commodities; fisheries; fishery policy; political; property; rights; saltwater fishing